Dziwny obłęd umysłowy małej entuzjastki. Korespondencja Marii von Herbert z Immanuelem Kantem jako fan mail - Urbańczyk, Agnieszka (Przestrzenie Teorii, 2023)
The paper discusses the letter exchange between Maria von Herbert and Immanuel Kant as an early example of fan mail. While the past research on Herbert described her as a sharp but underappreciated philosopher, in this paper she is treated primarily as a fangirl. The article discusses her correspondence with Kant (and Kant’s correspondence about her exchanged with others), her use of religious language as best means of conveying her fascination with an inaccessible celebrity, the parasocial interaction of these two, and the manner in which a hysterical discourse has been imposed on the young woman, not unlike the fate of contemporary fangirls.